2013
DOI: 10.1002/jat.2886
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol-induced apoptotic cell death in mouse TM4 Sertoli cells via the generation of reactive oxygen species and activation of the ERK signaling pathway

Abstract: Nonylphenol (NP), a representative endocrine disruptor, interferes with reproductive function in aquatic organisms and animals. Although many previous studies have focused on apoptotic cell death by NP, the fundamental mechanism of NP on apoptosis remains poorly understood. Here, we investigated the molecular mechanism on NP-induced apoptotic cell death in mouse TM4 Sertoli cells. To evaluate NP treatment on cell viability, formazan and lactate dehydrogenase (LDH) assays were performed. Results indicate that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 46 publications
1
36
1
Order By: Relevance
“…Interestingly, Choi et al (2013) have been confirmed that 4-NP reduced TM4 cell viability and induced apoptotic cell death, which was mediated via ROS generation and activation of the ERK signaling pathway in TM4 cells. Apparently, in their study, the concentrations of 4-NP (0, 5, 10, 15, 20 or 50 g/mL), equivalent to 0, 22.70, 45.40, 68.10, 90.81 and 227.03 M, were much higher than those in the environment and diet exposure as mentioned above.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, Choi et al (2013) have been confirmed that 4-NP reduced TM4 cell viability and induced apoptotic cell death, which was mediated via ROS generation and activation of the ERK signaling pathway in TM4 cells. Apparently, in their study, the concentrations of 4-NP (0, 5, 10, 15, 20 or 50 g/mL), equivalent to 0, 22.70, 45.40, 68.10, 90.81 and 227.03 M, were much higher than those in the environment and diet exposure as mentioned above.…”
Section: Introductionmentioning
confidence: 81%
“…High levels of specific EDCs are known to cause endocrine, reproductive, or neurological problems. Studies found that cells treated with 200 M NP exhibited a one hundred percent mortality or apoptosis response (Choi et al, 2013;Kuo et al, 2010). Health impacts of low-level exposure to EDCs are not as well known.…”
Section: Introductionmentioning
confidence: 97%
“…The MAPKs can be grouped into three main families: ERKs (extracellular-signal-regulated kinases), JNKs (Jun amino-terminal kinases), and p38/SAPKs (stress-activated protein kinases) [15,16] Lee et al find that 1,3-dinitrobenzene induces apoptosis via the JNK/MAPK pathway, whereas nonylphenol causes apoptosis via the ERK pathway [17,18]. Furthermore, BPA reduces Sertoli cells TF secretion through the ERK pathway which may impair spermatogenesis [19].…”
Section: Introductionmentioning
confidence: 97%
“…NP activates endoplasmic reticulum stress response, Fas/FasL, MAPKs, Akt and JNK signaling pathways, resulting in changes in cell survival, cell cycle progression and apoptosis (Choi et al 2014;Duan et al 2016c;Lepretti et al 2015;Liu et al 2015;Yao et al 2005). Importantly, our previous study outlined that NP treatment triggers Sertoli cell (SC) autophagy, probably through the ROS-mediated AMPK-mTOR pathway (Duan et al 2016c).…”
Section: Introductionmentioning
confidence: 98%
“…Accumulating studies have revealed that NP toxicity induces oxidative stress through the generation of ROS and stimulates apoptosis in a variety of cell types, including human embryonic stem cells, TM4 SCs and testicular SCs (Choi et al 2014;Gong et al 2009;Kim et al 2006;Kuo et al 2012;Zhang et al 2014). NP activates endoplasmic reticulum stress response, Fas/FasL, MAPKs, Akt and JNK signaling pathways, resulting in changes in cell survival, cell cycle progression and apoptosis (Choi et al 2014;Duan et al 2016c;Lepretti et al 2015;Liu et al 2015;Yao et al 2005).…”
Section: Introductionmentioning
confidence: 99%